La Realtà Virtuale al servizio della Didattica - Andreoli, Marco (Studi sulla Formazione/Open Journal of Education, 2018)
Towards the end of the Fifties film director Morton Heilig, universally known as the Father of Virtual Reality, presented the world with a prototype named Sensorama. Today, after nearly 70 years, that dream may be about to come true: thanks to technological progress, which has finally met the standards of Heilig’s brainchild, and to the huge financial investments made by the gaming industry, virtually anyone will have the opportunity to live a life-like, and at the same time unconventional, full-sensory experience. However, far beyond the Entertainment industry, the potential applications of Virtual Reality could branch off in several areas of interest; in particular, it could have a significant impact on the field of Education. While a large number of major universities throughout the US and the technologically advanced Asia are not only implementing experimental VR projects, but also producing significative results in terms of knowledge acquisition, the theme of our debate is this: is it possible for a system, conceived and created with entertainment as its ultimate purpose, to become the cornerstone of a worldwide Didactic Revolution?